Identification of components in extracts of Hericium erinaceus (Bull.: Fr.) pers that stimulate in vitro neurite outgrowth of NG108-15 / Wong Yuin Teng - Wong, Yuin Teng (2012)
Hericium erinaceus, locally known as cauliflower mushroom, and elsewhere as lion’s mane mushroom, Houtou (monkey head mushroom), Yamabushitake and Harisenbon (balloon fish), is an edible mushroom. It is well known for its medicinal and nutritional values. Hericium erinaceus is reported to have good anti-tumor properties and nerve tonic effects. Although H. erinaceus is a temperate mushroom, it has been successfully cultivated in Malaysia. However, there are very few reported studies on the chemical constituents that stimulate the neurite outgrowth for the locally cultivated species. The crude aqueous ethanol extract of H. erinaceus and its fractionated extracts (hexane, ethyl acetate and water) were evaluated for their effect in stimulating the neurite outgrowth using neural cell line NG108-15 whilst the Nerve Growth Factor (NGF) was used as the positive standard. The crude aqueous ethanol extract of H. erinaceus showed 15.0 % increase in neurite outgrowth at the concentration of 10.0 µg/ml. However, the crude aqueous ethanol extract showed decreased neurite growth as the dose was increased. The hexane, ethyl acetate and water fractions showed an increase in neurite outgrowth when the dose was increased exponentially (10.0, 25.0, 50.0 and 100.0 µg/ml). Maximum stimulation of neurite outgrowth was recorded with ethyl acetate fraction with 68.5 % increase compared to negative control followed by hexane fraction with 65.2 % increase. The combined fraction of hexane and ethyl acetate was further subjected to flash column chromatography. Among the 7 isolated fractions (fraction E1-E7), fraction E1 and fraction E2 show relatively higher neurite stimulation activity compared to other fractions. Maximum stimulation was recorded as 160.6 % increase and 149.1 % increase compared to negative control at the concentration of 100 µg/ml for fraction E1 and fraction E2 respectively. The chemical compositions of the fraction E1 of H. erinaceus were analayzed by GCMS. Four components were identified from fraction E1 comprising about 80.5 % of the total. Fraction E1 was made up of ethyl palmitate (29.8 %), ethyl stearate (2.3 %), ethyl oleate (18.6 %) and ethyl linoleate (29.9 %). Further isolation of fraction E2 using preparative TLC and HPLC gave subfraction sub4b_4 and subfraction sub4b_6. Subfraction sub4b_4 showed better neurite stimulation activity compared to subfraction sub4b_6 with 187.1 % increase in comparison. The chemical compositions of subfraction sub4b_4 and sub4b_6 were analyzed by NMR and LC/MS/MS. The components identified from subfraction sub4b_4 were hericenone C (and its isomer) and 4-(3’,7’-dimethyl-5’-oxo-2’,6’-octadienyl)-2-formyl- 3-hydroxy-5-methoxylbenzyl oleate (and its isomer). On the other hand, subfraction sub4b_6 comprised of hericenone C, 4-(3’,7’-dimethyl-5’-oxo-2’,6’-octadienyl)-2- formyl-3-hydroxy-5-methoxylbenzyl oleate and a phenolic component attached to the fatty ester side chain contained 26 carbons with 3 double bonds.